Stereotactic radiotherapy of vestibular schwannoma : Hearing preservation, vestibular function, and local control following primary and salvage radiotherapy - Putz, Florian; Müller, Jan; Wimmer, Cornelia; Goerig, Nicole; Knippen, Stefan; Iro, Heinrich; Grundtner, Philipp; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian (Strahlentherapie und Onkologie, 2017)
OBJECTIVE: The aim of this publication is to present long-term data on functional outcomes and tumor control in a cohort of 107 patients treated with stereotactic radiotherapy (RT) for vestibular schwannoma. PATIENTS AND METHODS: Included were 107 patients with vestibular schwannoma (primary or recurrent following resection) treated with stereotactic RT (either fractioned or single-dose radiosurgery) between October 2002 and December 2013. Local control and functional outcomes were determined. Analysis of hearing preservation was limited to a subgroup of patients with complete audiometric data collected before treatment and during follow-up. Vestibular function test (FVT) results could be analyzed in a subset of patients and were compared to patient-reported dizziness. RESULTS: After a mean follow-up of 46.3 months, actuarial local control for the whole cohort was 100% after 2, 97.6% after 5, and 94.1% after 10 years. In patients with primary RT, serviceable hearing was preserved in 72%. Predictors for preservation of serviceable hearing in multivariate analysis were time of follow-up (odds ratio, OR = 0.93 per month; p = 0.021) and pre-RT tumor size (Koos stage I-IIa vs. IIb-IV; OR = 0.15; p = 0.031). Worsening of FVT results was recorded in 17.6% (N = 3). Profound discrepancy of patient-reported dizziness and FVT results was observed after RT. In patients with primary RT, worsening of facial nerve function occurred in 1.7% (N = 1). CONCLUSION: Stereotactic RT of vestibular schwannoma provides good functional outcomes and high control rates. Dependence of hearing preservation on time of follow-up and initial tumor stage has to be considered.
EVALuna2:32910